Uranium mining and milling sites as sources of technologically-enhanced naturally occurring radioactive materials - Dudar, T.V. (Problems of Atomic Science and Technology, 2023)
Data on the uranium deposits database for the identification of radioactive material and sources of natural radiation within the Ukrainian Crystalline Shield are provided. The territories of uranium ore mining and processing are considered from the point of technologically enhanced naturally occurring radioactive materials view according to the proposed classification of uranium legacy sites. Measures to refer the uranium mining and processing sites to the “legacy” category of Ukraine are presented. Наведено дані щодо бази даних уранових родовищ для ідентифікації радіоактивного матеріалу та джерел природної радіації в межах Українського кристалічного щита. Території видобування і перероблення уранової сировини розглядаються, з точки зору техногенно-підсилених джерел радіоактивності природного походження, за запропонованою класифікацією потенційних об’єктів уранової спадщини. Представлено заходи щодо визначення об’єктів уранової спадщини України.